Current Knowledge on Factor V Leiden Mutation as a Risk Factor for Recurrent Venous Thromboembolism: A Systematic Review and Meta-Analysis - Eppenberger, Daria; Nilius, Henning; Anagnostelis, Betsy; Huber, Carola A.; Nagler, Michael (Frontiers in Cardiovascular Medicine, 2022)
Background: Thrombophilia screening is widely done in clinical practice, and it is claimed that the extent of venous thromboembolism (VTE) recurrence risk in patients with common defects is still not fully understood. Aim: We aimed to summarize all high-quality data of epidemiological studies prospectively observing VTE recurrence in patients with and without heterozygous factor V Leiden (FVL) mutation in various subgroups. Methods: We searched MEDLINE and EMBASE databases for cohort studies prospectively assessing VTE recurrence in patients with and without FVL mutation (PROSPERO: CRD42021182800). Data were extracted on cohort and study-level. The methodological quality was assessed using the Newcastle-Ottawa Scale (NOS). Relative risks (RR) were calculated overall and in subgroups using a fixed-effects model. Results: From 31 cohorts, 24 studies were finally included summarizing 13’571 patients. Heterozygous FVL mutation was identified in 2840 individuals (21%). The methodological quality was estimated to be high in 20 studies (83%). The overall RR was 1.42 (95% CI 1.29, 1.56), consistent across subgroups. Conclusions: Pooling all high-quality epidemiological data, the risk of recurrent VTE was increased by 42% in patients with heterozygous FVL mutation. Against the background of established risk factors, the FVL mutation plays only a marginal role in the risk assessment for recurrent VTE.